2017
DOI: 10.4103/ijpsym.ijpsym_120_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endocrine Parameters as Predictor of Major Depressive Disorder

Abstract: Background: The diagnosis of the disease, major depressive disorder (MDD), entirely depends on the presence of some symptoms without any biochemical parameter to support it. Depletion of dopamine though is an established feature, is not the sole causative factor of MDD. Moreover, it has very little diagnostic value due to a short half-life. Other chemical messengers like hormones have also been found to get altered due to significant over activity of hypothalamo-pituitary axis. Literature review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Elevation in PRL inhibits the pulsatile release of LH and FSH, which inhibits the production of testosterone by the gonads. Gupta et al ( 2017 ) concluded that plasma PRL was higher in individuals with MDD than in healthy controls and among women than in men, which is similar to the findings of our study. Historically, PRL levels recorded shortly after a seizure (within 20 mins) have been used to assess the etiology (epileptic or non-epileptic) of an epilepsy spell.…”
Section: Discussionsupporting
confidence: 92%
“…Elevation in PRL inhibits the pulsatile release of LH and FSH, which inhibits the production of testosterone by the gonads. Gupta et al ( 2017 ) concluded that plasma PRL was higher in individuals with MDD than in healthy controls and among women than in men, which is similar to the findings of our study. Historically, PRL levels recorded shortly after a seizure (within 20 mins) have been used to assess the etiology (epileptic or non-epileptic) of an epilepsy spell.…”
Section: Discussionsupporting
confidence: 92%
“…Both GAD as well as MDD were more associated with females compared to males in our study. Similar finding was observed in previous studies related to MDD by Charnsil et al, (4) Mahendra et al, (14) and Hazarika et al, and Gupta et al, (5) Zhicheng et al, also reported higher prevalence of MDD as well as GAD in females suggesting that female's patients need additional attention and their results showed that women who were unmarried, had low education, low per capita income and menopausal transition had significant association with more risk of GAD as well as MDD (15).…”
Section: Generalized Anxiety Disorder (Gad) and Major Depressive Diso...supporting
confidence: 91%
“…In depressive patients, 21% prevalence of thyroid dysfunction was seen (4). Patho-physiology of MDD is yet not established clearly (5). Thyroid disorder patients are prone to show depressive symptoms and depressive patients also may show thyroid abnormalities and thyroid hormone supplements have shown to improve the clinical response to antidepressant medications (6).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that TSH, TG and LDL-C were factors associated with elevated fasting glucose in overweight/obese FEDN MDD patients, with the elevated fasting glucose group being significantly higher than the normoglycemic group. The reasons and mechanisms for this phenomenon may be as follows: First, the concentration of 5-hydroxytryptamine in the brain is reduced in patients with major depression, leading to an increase in the concentration of thyrotropin-releasing hormone (TRH), which accelerates the secretion of TSH ( 28 ). Increased serum TSH can then act on TSH receptors in adipocytes to inhibit adipose triglyceride lipase, which in turn causes increased storage of triglycerides and an increase in adipocyte size, ultimately leading to overweight or obesity ( 29 ).…”
Section: Discussionmentioning
confidence: 99%